Coastal halophilous Limonium communities from West Iberian Peninsula - Costa, José Carlos (2015)
In the present work, we studied seven communities occurring in salt marshes in the west of the Iberian Peninsula, mostly ascribable to Sarcocornietea fruticosae class. Three new syntaxa are described: Myriolimo diffusi-Limonietum algarvensis, Triglochino maritimae-Sarcocornietum alpini subass. puccinellietosum maritimae and Limonion lanceolati-algarvensis. The first one is a chamaephytic community existing on thermomediterranean dry salt marshes, only inundated during high tides; it occupies welldrained sands from the Algarve (Coastal Lusitanian- Andalusian Province, Mediterranean Region), which the director species are the Iberian endemisms Myriolimon diffusum and Limonium algarvense. The second one is a halophytic community formed by Sarcocornia perennis subsp. alpini, Triglochin maritima, Halimione portulacoides, Puccinellia maritima, and Plantago maritima on sites occasionally inundated by saltwater, rich in sand and silt, north of the Ria de Aveiro (Miniense District, Cantabrian- Atlantic Subprovince, Eurosiberian Region). The last one is the alliance Limonion lanceolati-algarviensis, formed by Limonium sp. pl. communities from the Coastal Lusitanian-Andalusian Province. We also extend the distribution area of Puccinellio tenuifoliae- Limonietum plurisquamati to the Tagus estuary We propose the segregation between Myriolimetum ferulacei, from the Algarve sea cliffs, and Inulo crithmoidis- Myriolimetum ferulacei, from salt marshes